1987
DOI: 10.1084/jem.165.3.601
|View full text |Cite
|
Sign up to set email alerts
|

The isolation and sequence of a novel gene from a human functional T cell line.

Abstract: The study of T cell activation, proliferation, and effector function has been in vitro cultures of clonal T cell lines (1-3). Growth of such cell lines depends on periodic stimulation with growth factors, including IL-2, and with antigen that is recognized by the Ti/CD3 cell surface complex. It is believed that these IL-2-dependent, antigen-specific T cell lines, which function in vitro as helper or cytolytic cells, are normal counterparts of the T lymphocytes that perform these important effector and regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 31 publications
0
80
0
1
Order By: Relevance
“…One of the genes most overexpressed in CD8 ϩ CD57 ϩ (vs CD8 ϩ CD57 Ϫ ) cells codes for granulysin. This protein is present in the cytotoxic granules of CTL and NK cells and is a critical effector of the antimicrobial activity of CTLs against intracellular pathogens (37,38). Granulysin is also a chemoattractant and a proinflammatory activator that actively recruits immune cells to inflammation sites (39), and its presence shows that the antiviral role of CD8 ϩ CD57 ϩ cells involves mechanisms other than direct lysis of HIV-infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…One of the genes most overexpressed in CD8 ϩ CD57 ϩ (vs CD8 ϩ CD57 Ϫ ) cells codes for granulysin. This protein is present in the cytotoxic granules of CTL and NK cells and is a critical effector of the antimicrobial activity of CTLs against intracellular pathogens (37,38). Granulysin is also a chemoattractant and a proinflammatory activator that actively recruits immune cells to inflammation sites (39), and its presence shows that the antiviral role of CD8 ϩ CD57 ϩ cells involves mechanisms other than direct lysis of HIV-infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…A third mechanism involving direct T cell antimicrobial activity was suggested from studies identifying granulysin (1) in cytoplasmic granules of cytolytic T cells (2,3). Granulysin is a member of the saposin-like protein (SAPLIP) 3 family, including amoebapores, antimicrobial proteins that amoebas use to prevent growth of phagocytosed bacteria (4).…”
mentioning
confidence: 99%
“…It has been reported that there are two independent granulysin secretion pathways: one is Ca-independent and another is Ca-dependent [15,23]. In an earlier paper, we reported that serum granulysin levels increase gradually after 40 years old and that an increase of serum granulysin represents recovery and maturation of immune function after cell therapy for the immune compromised patients over a long time scale.…”
Section: Discussionmentioning
confidence: 81%
“…Granulysin is a recently defined cytolytic granule protein of NK cells and cytotoxic T lymphocytes (CTLs) [15]. Granulysin is synthesized as a 15-kDa precursor form, which is then sorted to the cytolytic granules and processed there into a 9-kDa effector form [16].…”
Section: Introductionmentioning
confidence: 99%